Evaluation of the Teacher Mobilizer Program at the Junior High School Level in Sleman Regency - Wira Berkat Anugerah Halawa; Priadi Surya (International Journal of Social Sciences and Humanities, 2026)
This study aims to evaluate: (1) the context of the Teacher Mobilizer Program at the junior high school level in Sleman Regency, (2) the input of the program, (3) the implementation process, and (4) the product or outcomes of the program. This study employs an evaluative research method with a qualitative approach. The research was conducted at SMP Negeri 3 Turi, SMP Negeri 1 Pakem, and SMP Negeri 1 Cangkringan, involving four Teacher Mobilizers (three of whom serve as principals) and three fellow teachers as informants. Data were collected through interviews, observations, and documentation studies. Data analysis used the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing/verification. Data validity was ensured through source triangulation and technique triangulation. The findings indicate that: (1) the program is relevant to the educational needs in Sleman Regency, especially in addressing one-way learning practices that are not student-centered; (2) in terms of input, teacher readiness is generally good, although infrastructure and technology support remain uneven; (3) the implementation process is effective, but there are inconsistencies between field practices and implementation guidelines, as well as variations in quality across learning groups; and (4) the program has improved teacher competence and paradigms, although the sustainability of practices and the equitable distribution of impact still need improvement.